Preliminary study on the Physical and Mechanical Properties of Tapioca Starch / Sugarcane Fiber Cellulose Composite - ABD RAZAK , JEEFFERIE; Othman, Nurul Fariha; Abd Rashid , Mohd Warikh; YAAKOB, MOHD YUHAZRI; Sihombing, Haeryip; Junid , Ramli (2006-2014 Asian Research Publishing Network (ARPN), 2011)
This study is to investigate the potential application of Tapioca Starch (TS) and Sugar Cane Fiber Cellulose (SCFC) as a green composite for disposable packaging food container. The experiment is started by preparing and characterizing the SCFC through various characterization tools, whereby the effect of various SCFC loading to the fabricated TS composites was then studied to find the best formulation for TS/SCFC composites. Various engineering properties for TS/SCFC composites were tested out to determine the mechanical and physical properties, beside the fracture morphology by using the optical microscope observation. Through the morphological view on the mechanical and physical testing fractured surfaces, it had significantly indicates the reinforcement role of various fiber loading into the resulted properties of produced composites. Although the results have shown good performance of composites for both mechanical and physical properties, but the adhesion between SCFC and TS matrix were not well attached. In overall, the development of this new material for food packaging application will provide great potential solution to the environmental friendly and safe packaging medium, either for food, consumer or environmental, as a whole.